DIPG-09. Diffuse Midline Glioma-Adaptive Combinatory Trial (DMG-ACT): A biology-driven platform trial in pediatric and young adult patients with diffuse midline glioma. (3rd June 2022) - Franson, Andrea; Kline, Cassie; Molinaro, Annette; Zhang, Yalan; Hitchner, Kelly; Koschmann, Carl; Nazarian, Javad; Mueller, Sabine
Abstract: BACKGROUND: Despite advances in our understanding of the biology of diffuse midline gliomas (DMGs), little progress has been made in improving outcomes. Therapy development is limited by lack of preclinical data across multiple model systems and laboratories; limited knowledge about blood-brain barrier penetrance; and lack of multi-agent therapies. We aim to address these issues through DMG-ACT, where we translate robust preclinical data using ONC201 as the therapy backbone in a multi-arm, combination strategy within an innovative trial design. DESIGN: DMG-ACT is an open-label, multi-institutional trial of combination therapy for patients with DMG between 2 and 39 years of age. The trial utilizes a novel Bayesian drug combination platform design with adaptive shrinkage (ComPAS). ComPAS allows ongoing assessment of therapy efficacy with borrowing of data across different arms and the ability to eliminate ineffective drug combinations and add new promising combinations throughout the trial. ONC201 is the backbone therapy in each arm and given in combination with other agents that show additive or synergistic benefit in preclinical testing. Patients enter into one of three cohorts: newly diagnosed (Cohort 1), post-radiation (Cohort 2), and relapsed/progressive (Cohort 3). The cohorts offer a target validation option to assess intratumoral pharmacokinetics and pharmacodynamics of drug given prior to tumor biopsy. Cohort 1 and 3 offer radiation or re-irradiation with concomitant single agent therapy followed by maintenance combination therapy. The primary efficacy endpoints are median progression-free survival at 6 months (Cohort 1 and 2) and overall survival at 7 months (Cohort 3). Exploratory endpoints include intratumoral drug concentration, toxicity profile of combination therapy during radiation therapy, toxicity profile and efficacy of combination therapy, CSF and ctDNA analysis, and health related quality of life, cognitive, and patient/proxy-reported outcome measures. This trial was successfully launched in November 2021 with updates to be presented at the meeting.